Dynamical Processes in Generalized Continua and Structures - Altenbach, Holm; Belyaev, Alexander; Eremeyev, Victor A.; Krivtsov, Anton; Porubov, Alexey V. (Advanced Structured Materials,, 2019)
This book presents a collection of chapters on the current problems of the theory of dynamical processes in generalized continua and structures, and has been compiled to commemorate the 70th birthday of Prof. Dmitry Indeitsev - a leading specialist in the field of dynamical processes in solids, fluids and structures. It discusses various applications related to Prof. Indeitsev's contributions, including various discrete and continuous dynamic models of structures and media, as well as a number of dynamical processes in generalized media.